Kebijakan Selektif Keimigrasian terkait Pembatasan Pemberian Bebas Visa Kunjungan pada Masa Pandemi Covid-19 (Selective Immigration Policy regarding Restrictions on Granting Free Visit Visas during the Covid-19 Pandemic) - Novianti Novianti (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2021)
The influx of hundreds of foreigners after the issuance of the application of the free visit visa has raised concerns of many parties that there will be an increase in the spread of Covid-19. This writing aims to determine the selective policies carried out by immigration related to restrictions on granting free visit visas during the Covid-19 pandemic. This paper uses a normative juridical research method which is analyzed descriptive-qualitatively using library data. The results of the study revealed that the restrictions on the granting of free visit visas and stay permits for foreigners during the Covid-19 pandemic were carried out through several issuances of the Minister of Law and Human Rights Regulations (Peraturan Menteri Hukum dan Hak Asasi Manusia, Permenkumham), namely Permenkumham Numbers 3, 7, 8, 11, and 26 of 2020, as well as PermenkumhamNumber 27 of 2021. Some of these Permenkumham have been replaced several times, and the last one was Permenkumham Number 34 of 2021. The selective immigration policy during the Covid-19 pandemic was to limit the granting of free visit visa with some exceptions and grant entry permits to foreigners at the time of implementation of restrictions on community activities (Pemberlakuan Pembatasan Kegiatan Masyarakat, PPKM). For this reason, the government needs to introduce strict policies by screening and quarantining foreigners who enter Indonesian territory to prevent transmission of Covid-19. AbstrakMasuknya ratusan orang asing pasca diterbitkannya pemberlakuan pemberian bebas visa kunjungan menimbulkan kekhawatiran banyak pihak akan terjadi peningkatan penyebaran Covid-19. Penulisan ini bertujuan untuk mengetahui kebijakan selektif yang dilakukan oleh keimigrasian terkait pembatasan pemberian bebas visa kunjungan pada masa pandemi Covid-19. Tulisan ini menggunakan metode penelitian yuridis normatif yang dianalisis secara deskriptif-kualitatif dengan menggunakan data kepustakaan. Hasil penelitian mengungkapkan pengaturan pembatasan pemberian bebas visa kunjungan dan izin tinggal bagi orang asing pada masa pandemiCovid-19 dilakukan melalui beberapa penerbitan Peraturan Menteri Hukum dan Hak Asasi Manusia (Permenkumham) yakni Permenkumham Nomor 3, 7, 8, 11, dan 26 Tahun 2020, serta Permenkumham Nomor 27 Tahun 2021. Beberapa Permenkumham tersebut telah dilakukan beberapa kali penggantian dan terakhirdiberlakukan Permenkumham Nomor 34 Tahun 2021. Kebijakan selektif keimigrasian pada masa pandemi Covid-19 yakni melakukan pembatasan pemberian bebas visa kunjungan dengan beberapa pengecualian dan memberikan izin masuk kepada orang asing pada saat pemberlakuan pelaksanaan pembatasan kegiatan masyarakat (PPKM). Untuk itu pemerintah perlu melakukan kebijakan yang ketat dengan melakukan skrining dan karantina terhadap orang asing yang masuk ke wilayah Indonesia untuk mencegah penyebaran Covid-19.